Analysis of Digitalization Readiness in the Administrative Information Service System for Early Childhood Education in Rokan Hilir Regency - Khoiroh, Fhatia; Natuna, Daeng Ayub; Mahdum, Mahdum (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the digitalization of the administrative information service system for early childhood education in Rokan Hilir Regency. Using an exploratory qualitative approach, the research was conducted at the Department of Education and Culture of Rokan Hilir Regency through documentation, observation, and in-depth interviews with relevant informants. Data analysis referred to six main components of the information system, namely hardware, software, procedures, human resources, databases, as well as data networks and data communities. The results of the study show that the implementation of administrative digitalization for early childhood education in Rokan Hilir Regency still faces various obstacles. The availability of hardware and software is uneven, digitalization procedures have not been consistently applied, and human resource competencies need to be improved. In addition, digital database management remains limited due to infrastructure and human resource constraints, while internet access and participation in data communities are still suboptimal, especially in coastal and remote areas. Therefore, efforts to improve infrastructure, provide human resource training, and strengthen data communities are necessary to support the effective and equitable implementation of administrative digitalization in early childhood education institutions in Rokan Hilir Regency.